Guideline for the Graphic Design of Web Application for Children’s Interface - Tengku Siti Meriam Tengku Wook; Siti Salwah Salim (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
There have been numerous studies done on the guidelines of user interface, but only a number of them have considered specific guidelines for the design of children’s interface. This paper is about a research on the specific guidelines for children, focusing on the criteria of graphic design. The objective of this research is to study on the guidelines of user interface design and to develop specific guidelines on children’s graphic design. The criteria of graphic design are the priority of this research since previous research have proven that graphic design is the main factor which contributes to the problem of usability of web application interfaces, in terms of the overall graphic layout not being in a hierarchical order, not taken into concern the availability of space, inappropriate margin, improper type and font size selection, and less concentration on the use of the colours. The research methodology makes use of the comparison of and the coordination to the guidelines on children’s interface and the specific guidelines on the graphic design of web application interfaces. The contribution of this research is the guidelines on the design of web application graphics which are specifically for children. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2658